Chromosome numbers and karyotypes of some taxa of genus Artemisia (Asteraceae, Anthemideae) subgenus Dracunculus (Bess.) Rydb - Tabur, Selma; Civelek, Semsettin; Oney, Signem; Yilmaz, Sadiye Betul; Kursat, Murat (Firenze Univ Press, 2011)
Chromosome numbers and karyotypes of four taxa of genus Artemisia subgenus Dracunculus were investigated. Chromosome numbers of three varieties (var. campestris, var. marschalliana and var. araratica) of Artemisia campestris were found as 2n=4x=36. In the present work, chromosome number of A. campestris var. araratica and detailed karyotypes of A. campestris var. marschalliana and A. scoparia are presented for the first time. The chromosome complement of A. campestris var. marschalliana (2n=4x=36) consists of 28 median and eight submedian chromosomes. That of A. scoparia (2n=2x=16) consists of 16 median- centromeric chromosomes. We believe that these karyological data will enhance the karyological knowledge of subgenus Dracunculus and will prove to be an important source of information for new researches relating to genus.
Keywords: Artemisia; chromosome numbers; Dracunculus; karyotype; Turkey